2016
DOI: 10.1590/s0100-204x2016000500031
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus type 1 in cumulus-oocyte complexes collected from naturally infected cows

Abstract: -The objective of this work was to investigate the presence of bovine herpesvirus type 1 (BoHV-1) in follicular fluid and in cumulus-oocyte complexes (COC) recovered from naturally infected cows but with no clinical signs of the disease. Cows that were seropositive (n=38) or seronegative (n=8, control) to infectious bovine rhinotracheitis were selected after a serum neutralization test in microplates. The presence of the virus was investigated by PCR in COC and in follicular fluid. Viral DNA was not found in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Researchers using the polymerase chain reaction (PCR) test to detect BoHV-1 DNA have concluded that the risk of transmission of BoHV-1 by COCs and follicular fluid from seropositive cows without clinical symptomatology is irrelevant (Oliveira et al 2016), since the presence of viral DNA was not observed in any of their tested samples.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers using the polymerase chain reaction (PCR) test to detect BoHV-1 DNA have concluded that the risk of transmission of BoHV-1 by COCs and follicular fluid from seropositive cows without clinical symptomatology is irrelevant (Oliveira et al 2016), since the presence of viral DNA was not observed in any of their tested samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of trypsin washing for decontamination of in vitro-produced bovine embryos is controversial. 16 In support of this contention, while several studies demonstrated that trypsin treatment is very effective for the removal or inactivation of BoHV-1, 7,10,17 other investigators found that the inclusion of trypsin solution in the washing procedure may be sufficient to strip BoHV-1 from the surface of the embryo but has no such effect on virus particles once inside. 14,18,19 Bielanski and Lalonde demonstrated that embryo cryopreservation may be regarded as a safety measure to decrease the potential risk or even mitigate disease transmission by embryo transfer.…”
Section: Methods For Virus Removal From Embryosmentioning
confidence: 98%